Eenergy effiency access strategy:towards hybrid wireless sensor network - Ya-song WANG; Qin-yu ZHANG; Yun-he LI; Jing HAN (Tongxin xuebao)
A dynamically access mechanism of non-real-time sensor nodes with adaptive listening and sleeping,against the background,co-existence of real-time traffic and non-real-time traffic in the networks,was studied.The energy consumption is very slow while the node is in a sleep state; however,the long sleep time may make the network nodes miss transmission opportunity.Thus,according to the usage of the channel,a reasonable set of wireless sensor network nodes sleep time in the network energy consumption and transmission efficiency could be adjusted to maximize the energy transmission efficiency of wireless sensor network.Firstly,the continuous-time Markov modeling the problem was used and analyzed.Then system model based on perturbation analysis theory was proposed to obtain the gradient algorithm for solving the optimal sleep time.Finally,the feasibility of the recommended program is verified by comparing the theoretical results and computer simulation.